Geochemical composition of surface sediments near Isla de Sacrificios coral reef ecosystem, Veracruz, Mexico - Rosales-Hoz, Leticia; Kasper-Zubillaga, Juan Jose; Carranza- Edwards, Arturo; Hernández, Omar Celis (HIDROBIOLÓGICA, 2017)
Twenty three surface sediment samples were collected in the area surrounding the Isla de Sacrificios located in the southwestern Gulf of Mexico. The temporal impact of natural discharges in the area was evaluated through the study of the textural and chemical characteristics of the sediments that surround the Veracruz Reef System. The particle size during the three sampled seasons was associated with the prevailing energy conditions. The degree of influence of terrigenous sediments was evaluated through the content of Al2O3, SiO2, Na2O and K2O, which is higher in October (2004) compared to June (2004) and/or February (2005) due to the rainy season. It was observed that gravel, CaO and CO3 were significant variables grouped in Factor 1 that suggested that gravel-sized fractions are produced by the abrasion of the reef in February (2005) and being correlated with other variables in June (2004). Another groupings were among SiO2, CaO, K2O, CO3, for October (2004) which suggested dilution of carbonates due to the terrigenous input. In addition, the factor analysis showed that grain size and heavy minerals represented by TiO2, MnO, MgO and Fe2O3 have a major importance in February (2005) associated with fluvial discharges. The factor analysis showed that the sedimentological and geochemical characteristics of the sediments varied throughout the different seasons. A correlation among Al2O3 and Na2O, P2O5, y Fe2O3 and organic carbon in the three sampling seasons suggested that these chemical components have a terrigenous source.